Building flexibility revenue in modeled future bulk power systems with varying levels of renewable energy. Issue 7 (July 2022) - Zhou, Ella; Hale, Elaine; Present, Elaina
Abstract: The buildings sector can provide important demand-side flexibility for the integration of renewable energy. With the changing power system and rapid advancement in building energy control technology, technology providers and demand response aggregators need to know what potential revenues could be obtained by providing grid services. We dispatch a normalized and parameterized model of building load shifting against marginal service prices from grid investment and operational models to produce a database of the capacity, energy, and ancillary service revenues (gross value of providing bulk power system services) for a marginal kilowatt-hour (kWh) of shiftable load. The database is geographically disaggregated, hourly, and parameterized so that flexibility value can be estimated for a wide range of building technologies. The database covers the contiguous United States under three 2030 grid scenarios. Given the high degree of uncertainty in such grid projections, the results are perhaps best interpreted in terms of regional climate and grid mixes and are thus potentially applicable in non-U.S. contexts. Upon analyzing the results, we find the monthly mean gross value of building load shifting is 0–38 cents/kWh-day and the daily gross value of shifting the highest-value hour each day can be up to 620 cents/kWh-day. The different revenues obtained by aggregating results in different ways, as well as observed regional and seasonal differences, suggest different building technologies and grid environments might call for demand response program designs and business models. Abstract : Power system flexibility; Demand-side management; Demand flexibility; Grid interactive efficient buildings.